Percutaneous left ventricular unloading of veno‐arterial extracorporeal membrane oxygenation with the atrial flow regulator. Issue 7 (9th April 2022) - Benseghir, Yassine; Pozzi, Matteo; Obadia, Jean François; Rioufol, Gilles
Abstract: The use of veno‐arterial extracorporeal membrane oxygenation (VA‐ECMO) has increased exponentially. Pulmonary congestion is a potentially life‐threatening complication of peripheral VA‐ECMO. Recently updated guidelines argue for a low threshold of left ventricular (LV) unloading. Although the optimal method of LV unloading is still a matter of debate, the percutaneous approaches became an increasingly used option over time. Here, we present a case of LV unloading with the Atrial Flow Regulator (Occlutech) in a patient supported with peripheral VA‐ECMO.